Evaluating the Effect of Historical - cultural Tourism on Stable Development of Kerman - Baratali Khakpoor; Mohsen Kamandari; Fahimeh Shafiee (جغرافیا و پایداری محیط)
Tourism industry is considered as an effective factor for economic and social development of urban areas. As a matter of fact, cities has always been regarded as one of the most attractive places for tourists which, as a symbol of the degree of human social evolution, include important economic, scientific, recreational, medical, centers. Moreover, they have natural attractions and cultural heritage. These features make cities attractive for tourists. However, if the tourist entrance to the cities were not accompanied by planning and management, it would not only stop the urban development and progress, but also make a lot of damages to these areas. Therefore, systematic analysis and comprehensive approach are necessary and inevitable to achieve a sustainable stable development of tourism according to the social, cultural, economic and environmental dimensions. Kerman, as one of the country's historic cultural center, attracts a large number of domestic and foreign tourists annually. The present study aims at evaluating the impact of historical and cultural tourism on stable development of Kerman. The Method is a descriptive - analytical one in which the data were gathered applying the field study and literature survey. Cochran formula was used to determine the samples, 384. Besides, sampling procedures and questionnaires were randomly distributed. The data were analyzed by applying Spss software. The findings which were the result of t-tests (one sample) and Spearman correlation, suggest that cultural-historical tourism has a positive impact on increasing the revenues in Kerman. Besides, the effects can be used to increase the income of citizens, create new jobs, and improve local businesses. Moreover, the effects of tourism on the stable development in dimensions (economic, social, and environmental) concluded that economic indicators index (0.763) has the maximum environmental impact, while bio-environmental coefficient (0.487) has the minimal effect on stable development in Kerman.